Diversity of mosquitoes and the aquatic insects associated with their oviposition sites along the Pacific coast of Mexico - Bond Compeán, Juan Guillermo; Casas Martínez, Mauricio; Quiroz Martínez, Humberto; Novelo Gutiérrez, Rodolfo; Marina Fernández, Carlos F.; Ulloa García, Armando; Orozco Bonilla, Arnoldo; Muñoz, Miguel; Williams, Trevor (2014)
Background: The abundance, richness and diversity of mosquitoes and aquatic insects associated with their oviposition sites were surveyed along eight states of the Pacific coast of Mexico. Diversity was estimated using the Shannon index (H’), similarity measures and cluster analysis. Methods: Oviposition sites were sampled during 2–3 months per year, over a three year period. Field collected larvae and pupae were reared and identified to species following adult emergence. Aquatic insects present at oviposition sites were also collected, counted and identified to species or genus. Results: In total, 15 genera and 74 species of mosquitoes were identified: Anopheles pseudopunctipennis, An. albimanus and Aedes aegypti were the most abundant and widely-distributed species, representing 47% of total mosquito individuals sampled. New species records for certain states are reported. Anopheline diversity was lowest in Sinaloa state (H’ = 0.54) and highest in Chiapas (H’ = 1.61) and Michoacán (H’ = 1.56), whereas culicid diversity was lowest in Michoacán (H’ = 1.93), Colima (H’ = 1.95), Sinaloa (H’ = 1.99) and Jalisco (H’ = 2.01) and highest in Chiapas (H’ = 2.66). In total, 10 orders, 57 families, 166 genera and 247 species of aquatic insects were identified in samples. Aquatic insect diversity was highest in Chiapas, Oaxaca and Michoacán (H’ = 3.60-3.75). Mosquito larval/pupal abundance was not correlated with that of predatory Coleoptera and Hemiptera. Conclusion: This represents the first update on the diversity and geographic distribution of the mosquitoes and aquatic insects of Mexico in over five decades. This information has been cataloged in Mexico’s National Biodiversity Information System (SNIB-CONABIO) for public inspection.